Accuracy of the random-incidence scattering coefficient measurement. (May 2016) - Shtrepi, Louena; Astolfi, Arianna; D'Antonio, Gianluca; Vannelli, Giuseppe; Barbato, Giulio; Mauro, Stefano; Prato, Andrea
Abstract: The experimental results presented in this study aim at providing an useful insight into the accuracy of the measurement procedure of the random-incidence scattering coefficient as defined in ISO 17497-1:2004. A systematic experimental investigation has been conducted in a full-scale reverberation room. The tested diffusers are characterized by different geometrical distributions of hollow wooden cubes with an edge length of 20 cm, and different configurations of the measurement set-up. The accuracy of the measurement results has been evaluated considering the contribution of the different undefined aspects of the ISO method such as the microphones height, the air gap underneath the turntable, the sample shape, and the correction of the effects of the absorption and scattering coefficients of the base plate. The results showed that the accuracy of the measurement increases when a more rigid turntable and a circular sample are used, and when the air gap below the turntable is covered. Furthermore, the distance of the microphones from the sample surface was found to affect significantly the results, thus to influence the accuracy of the measurements.